Safety and Quality Study of Innovation Product Instant Powder of Jamu Kunyit Asam - Rusmalina, Siska; Khasanah, Kharismatul; Loso, Loso; Mayangsari, Citra Cipta; Hadi, Nafis Daniel (KnE Social Sciences, 2024)
The surge in Indonesia’s interest in the “back to nature” paradigm drives an increased demand for herbal drink products, presenting a lucrative business opportunity. Instant powdered drinks, designed for extended shelf life, convenience, and ease of consumption, are at the forefront of this trend. The research team innovatively developed an instant herbal turmeric tamarind powder, capitalizing on the practicality of serving, consuming, portability, and prolonged shelf life. To ensure the safety and quality of these developed products, the research adopted an experimental approach, examining the impact of the instant turmeric powder production method on safety and quality parameters. The sample, an innovative instant turmeric tamarind powder product, underwent testing against BPOM standards, specifically BPOM Number 32 of 2019, which outlines Safety and Quality Requirements for Traditional Medicines. Assessed parameters included organoleptic characteristics, moisture content, and cadmium metal contamination. Research findings revealed lead and cadmium concentrations of 24,528 ppm and 0.1095 ppm, respectively, in the turmeric tamarind herbal powder formulation developed in a previous study (Siska et al., 2021). Consequently, the lead content exceeded the specified BPOM limit of ≤10 ppm, while the cadmium content complied with the set limit of ≤ 0.3 ppm. Despite the lead content exceeding regulatory thresholds, the innovative herbal turmeric tamarind instant powder product demonstrated safety and quality, indicating suitability for consumption even after undergoing the manufacturing process. The product exhibited characteristics, such as a crystalline powder form, a turmeric yellow color, a distinctive sour turmeric aroma, and a sweet and sour taste. Keywords: instan powder, jamu, kunyit asam, quality and safety